2019
DOI: 10.21475/ajcs.19.13.04.p989
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and nutrient extraction by Brachiaria brizantha fertigated with treated sewage effluent

Abstract: The present study was performed to evaluate the responses in productivity and nutrient extraction in dry biomass of Brachiaria brizantha ‘Marandu’ fertigated with treated sewage effluent (TSE) from 2013 to 2014, in Jaboticabal, São Paulo, Brazil. A triple line source sprinkler system was used to perform uniform but gradual irrigation of TSE and mineral fertilization in five treatments, with the following TSE fractions in water: 1.0 (E5); 0.87 (E4); 0.6 (E3); 0.31 (E2), and 0.11 (E1). In addition to fertigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…In springsummer, it accounted for 83% of dry matter production. Similar results were obtained by Dantas et al (2020), Santos et al (2019), and Dantas et al (2016) using the same forage and using increasing doses of fertigation, also obtained a reduction in fresh and dry mass in winter and an increase in dry and fresh mass in the spring-summer period.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In springsummer, it accounted for 83% of dry matter production. Similar results were obtained by Dantas et al (2020), Santos et al (2019), and Dantas et al (2016) using the same forage and using increasing doses of fertigation, also obtained a reduction in fresh and dry mass in winter and an increase in dry and fresh mass in the spring-summer period.…”
Section: Resultssupporting
confidence: 85%
“…In addition, the Brachiaria forage coefficient (kc) equal to 1.0 was used (SANTOS et al, 2019) to obtain the maximum crop evapotranspiration (ETo = ETc).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher TN concentration in the surface layer for treatments with higher TSE levels was due to the nutrient supply by TSE fertigation, in which TN effluent average content was 50.2 mg•dm -3 . Santos et al (2019) observed that one of the factors that promoted an increase in U. brizantha yield in treatments with a higher TSE level (E3 and E5) was the great availability of N in the soil. The authors observed that the amount of N extracted by U. brizantha in the E5 treatment were 1,045 kg•ha -1 in 2013 and 1.501 kg•ha -1 in 2014, while for the E1 treatment the extraction was only 491 and 404 kg•ha -1 , respectively.…”
Section: Resultsmentioning
confidence: 98%
“…If the amount of effluent to meet the nitrogen demand by the U. brizantha were greater than the amount of water required by the crop in a period of 28 days, the application of effluent would be based on nutritional demand, otherwise the water demand was used. For further details, check the studies by Santos et al (2017) and Santos et al (2019).…”
Section: Methodsmentioning
confidence: 99%